Mechanical properties of recycling chip aluminium 7075 through powder metallurgy technique - Yacob, Fariza Fuziana (2015)
This research has been carried out based on the recycling of 7075 aluminium alloy via powder metallurgy technique. Methods chose in recycling waste material is being concerned as one of the major issues. Recycled materials were obtained from 7075 aluminium alloy machining chips via powder metallurgy technique. Both ball milling time and sintering temperature have a positive effect on the mechanical properties. The main point in this research is to produce recycled 7075 aluminium alloy by using powder metallurgy technique. This is because by using conventional method, a lot of heat will be involved throughout the process and can pollute the environment. This powder metallurgy technique is propose in a way that this process can assist in saving the environment where minimal heat is used throughout the process. By using this technique, the environmental factor can be reduced other than saving energy and cost. In this research, recycled 7075 aluminium alloy with addition of alumina and graphite was produced. Physical and mechanical properties of the sample with and without addition of alumina and graphite are tested. Each property is then compared to determine which sample has better properties. All samples undergoes the same process which started with ball milling at 100, 150 and 200 rpm, pressed at pressure of 40 tonnes and sintered at three different temperatures which are 550, 600 and 650 °C. After sintering, the sample undergoes physical and mechanical testing. The microstructure of specimens were observed using Scanning Electron Microscopy (SEM) to study the surface morphology, while tensile test were measured by using a Universal Testing Machine (UTM). Besides, particle size distribution was measured using Particle Size Analyzer (PSA) for each speed of powder produced and green density was measured using electronic densimeter before and after the sintering process. Microhardness analysis was made using Vickers Hardness to measure the hardness of the samples after being sintered. Sample A8 (200 rpm ball milling, 650 °C sintering temperature, graphite reinforcement) point out as the highest sintered density of recycled 7075 aluminium alloy (2.681 g/cm3) with less porosity. The microhardness value with 71 Hv, 25.082 MPa tensile strength and 3.45 % elongation to failure were recorded as the maximum value obtained in the research by the same A8 sample. It is found that porosity, density, tensile strength and microhardness correlates to each other.